Molecular Identification and Antimicrobial Potential of Streptomyces Species from Nepalese Soil - Karan Khadayat; Dawa Dindu Sherpa; Krishna Prakash Malla; Sunil Shrestha; Nabin Rana; Bishnu P. Marasini; Santosh Khanal; Binod Rayamajhee; Bibek Raj Bhattarai; Niranjan Parajuli (International Journal of Microbiology)
Streptomyces are widely used for the production of secondary metabolites with diverse biological activities, including antibiotics. The necessity of alternative antimicrobial agents against multidrug-resistant pathogens is indispensable. However, the production of new therapeutics is delayed in recent days. Thus, the isolation of new Streptomyces species has drawn attention. Nepal—a country rich in biodiversity—has got high possibilities for the discovery of members of actinomycetes, especially in the higher altitudes. However, in vain, only a few screening research works have been reported from Nepal to date. Streptomyces species were isolated on ISP4 media, and characterization was performed according to morphological similarity and 16S rRNA sequence similarity using bioinformatic tools. Ethyl acetate extracts of Streptomyces species were prepared, and the antimicrobial activity was carried out using agar well diffusion technique. In this report, 18 Streptomyces species isolated from the soil were reported based on sequence analysis of 16S rRNA. Among them, 12 isolates have shown antibacterial activity against extended-spectrum beta-lactamase- (ESBL-) producing Escherichia coli. Here, we have also analyzed 16S rRNA in 27 Streptomyces species whose whole-genome sequence is available, which has revealed that some species have multiple copies of the 16S gene (∼1.5 kb) with significant variation in nucleotides. In contrast, some Streptomyces species shared identical DNA sequences in multiple copies of 16S rRNA. The sequencing of numerous copies of 16S rRNA is not necessary, and the molecular sequencing of this region is not sufficient for the identification of bacterial species. The Streptomyces species-derived ethyl acetate extracts from Nepalese soil demonstrate potential activity against ESBL-producing E. coli. Thus, they are potential candidates for antibiotics manufacturing in the future.